Analytical network-averaging of the tube model: Strain-induced crystallization in natural rubber. (July 2018) - Khiêm, Vu Ngoc; Itskov, Mikhail
Highlights: A novel constitutive model for SIC is proposed because all previous models deviate from calorimetric experimental data. All parameters for the crystallization kinetics can be directly taken from physical measurements. Crystallization nucleation and growth are bounded. The model automatically transforms to our theories on rubber elasticity and mechanically induced chemiluminescence. Abstract: In this contribution, we extend the analytical network-averaging concept (Khiêm and Itskov, 2016) to phase transition during strain-induced crystallization of natural rubber. To this end, a physically-based constitutive model describing the nonisothermal strain-induced crystallization is proposed. Accordingly, the spatial arrangement of polymer subnetworks is driven by crystallization nucleation and consequently alters the mesoscopic deformation measures. The crystallization growth is elucidated by diffusion of chain segments into crystal nuclei. The crystallization results in a change of temperature and an evolution of heat source. By this means, not only the crystallization kinetics but also the Gough–Joule effect are thoroughly described. The predictive capability of the constitutive model is illustrated by comparison with experimental data for natural rubbers undergoing strain-induced crystallization. All measurable values such as stress, crystallinity and heat source are utilized for the comparison.